Outcome of bystander cardiopulmonary resuscitation after out-of-hospital cardiac arrest in Beijing. Issue 2 (1st December 2021) - Shi, Xian; Wu, Yang; Li, Haibin; Ma, Shengkui; Li, Dou; Gao, Ding; Cui, Hao; Yu, Changxiao; Yang, Song; Tang, Ziren; Shao, Fei
Abstract: Aim: We aimed to investigate the association between bystander cardiopulmonary resuscitation (CPR) and survival of patients with out-of-hospital cardiac arrests (OHCA) in Beijing. Methods: This observational study analyzed adult patients with OHCA treated by the Beijing emergency medical service (EMS) from January 2013 to December 2017. Data were collected in a Utstein style with a 1-year follow-up and a primary outcome of survival to hospital discharge. Secondary outcomes were return of spontaneous circulation (ROSC), survival to admission, favorable neurological outcome at hospital discharge, and survival and favorable neurological outcomes of up to 1 year. Results: A total of 5016 patients with OHCA from Beijing's urban area were recorded by EMS, wherein 765 patients (15.25%) underwent bystander CPR. The data were propensity score-matched forage, sex, location, witness, aetiology, initial rhythm, and call to EMS arrival to compare the difference between the occurrence and nonoccurrence of bystander CPR. The survival upon the discharge of patients who experienced bystander CPR was superior to that of patients who did not receive bystander CPR (3.7% vs 1.2%, respectively; P < 0.001). Moreover, patients with OHCA resuscitated with bystander CPR achieved better outcomes of ROSC, survival to admission, favorable neurological outcome at hospital discharge, survival and favorable neurological outcome after 1 year compared with those who were not resuscitated with bystander CPR. Conclusion: Survival and neurological outcome of patients who underwent bystander CPR was better than those who underwent nonbystander CPR in Beijing. However, the rate of bystander CPR was low.